Immunogenic properties of nickel-doped maghemite nanoparticles and the implication for cancer immunotherapy - Lenka Rajsiglova; Michal Babic; Katerina Krausova; Pavol Lukac; Katerina Kalkusova; Pavla Taborska; Ludek Sojka; Jirina Bartunkova; Dmitry Stakheev; Luca Vannucci; Daniel Smrz (Journal of Immunotoxicology, 2024)
Nanoparticles are commonly used in diagnostics and therapy. They are also increasingly being implemented in cancer immunotherapy because of their ability to deliver drugs and modulate the immune system. However, the effect of nanoparticles on immune cells involved in the anti-tumor immune response is not well understood. The study reported here showed that nickel-doped maghemite nanoparticles (FN NP) are differentially cytotoxic to cultured mouse and human cancer cell lines, causing their death without negatively impacting the subsequent anticancer immune response. It also found that FN NP induced cell death in the mouse colorectal cancer cell line CT26 and human prostate cancer cell line PC-3, but not in the human prostate cancer cell line LNCaP. The induced cancer cell death did not affect the phenotype and responsivity of the isolated mouse peritoneal macrophages, or ex vivo-generated mouse bone marrow-derived, or human monocyte-derived dendritic cells. Additionally, the induced cancer cell death did not prevent the ex vivo-generated mouse or human dendritic cells from stimulating lymphocytes and enriching cell cultures with cancer cell-reactive T-cells. In conclusion, this study shows that FN NP could be a valuable platform for targeting cancer cells without causing immunosuppressive effects on the subsequent anticancer immune response.